1996
DOI: 10.1007/bf00227302
|View full text |Cite
|
Sign up to set email alerts
|

How humans combine simultaneous proprioceptive and visual position information

Abstract: To enable us to study how humans combine simultaneously present visual and proprioceptive position information, we had subjects perform a matching task. Seated at a table, they placed their left hand under the table concealing it from their gaze. They then had to match the proprioceptively perceived position of the left hand using only proprioceptive, only visual or both proprioceptive and visual information. We analysed the variance of the indicated positions in the various conditions. We compared the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
159
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(191 citation statements)
references
References 19 publications
17
159
2
Order By: Relevance
“…Inspection of each condition's scores on this variate showed that the greatest difference was between the P:P condition (score = 1.74, SD = 0.40) and both the V:P and VP:P conditions (scores = 1.27, SD = 0.32, and 0.99, SD = 0.27, respectively), though all pairwise comparisons were significant beyond the .05 level in protected post hoc tests. First, this result clearly replicates the findings ofWann (1991), von Hofsten andRosblad (1988), andvan Beers et al (1996) regarding the ordering of matching performance in the three conditions. VP:P shows the best performance, followed by V:P, followed by P:P. Second, the use of discriminant analysis shows that the differences between these conditions are primarily in the variable error in the X dimension.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Inspection of each condition's scores on this variate showed that the greatest difference was between the P:P condition (score = 1.74, SD = 0.40) and both the V:P and VP:P conditions (scores = 1.27, SD = 0.32, and 0.99, SD = 0.27, respectively), though all pairwise comparisons were significant beyond the .05 level in protected post hoc tests. First, this result clearly replicates the findings ofWann (1991), von Hofsten andRosblad (1988), andvan Beers et al (1996) regarding the ordering of matching performance in the three conditions. VP:P shows the best performance, followed by V:P, followed by P:P. Second, the use of discriminant analysis shows that the differences between these conditions are primarily in the variable error in the X dimension.…”
Section: Resultssupporting
confidence: 86%
“…These results were interpreted as evidence for sensorimotor integration, whereby a combined visual and proprioceptive representation oflocation in egocentric space is superior to a representation using just one of those modalities. Van Beers, Sittig, and Denier van der Gon (1996) found that the variable error of performance in a VP:P condition was smaller than expected from the variances of V:P and P:P performance, again suggesting integration. Additional studies (Baud-Bovy & Viviani, 1998;Helms-Tillery, Flanders, & Soechting, 1991 have focused specifically on proprioceptive representation but have used a memoryguided task in which the hand is replaced in a recently occupied location.…”
mentioning
confidence: 86%
“…This is the first evidence, to our knowledge, for a statistically significant improvement in hand localization ability in childhood when proprioception is added to vision von Hofsten & Rosblad, 1988;van Beers et al, 1996;King et al, 2010). The improvement was modest, and the present study may have been able to measure it because we used a relatively large number of trials per condition, and estimated distributions of points using a robust procedure (Rousseeuw, 1984).…”
Section: Discussionmentioning
confidence: 72%
“…The way this sensory input is processed depends on the demands of the motor task at hand; van Beers and colleagues (1999) have shown that motor performance is improved when one has access to information from multiple sensory modalities regarding limb position, when compared to information from only one source. Depending on the stage of movement planning Sabes 2003, 2005), target position (van Beers et al 1996(van Beers et al , 1998(van Beers et al , 1999, and target modality (Sober and Sabes 2005), the brain can select different combinations of sensory input (i.e. vision, proprioception) to localize one's hand.…”
Section: Goal-directed Movementmentioning
confidence: 99%